Transcriptomic and Metabolomic Analyses Reveal Differences in Flavonoid Synthesis During Fruit Development of Capsicum frutescens pericarp - Yinxin Yang; Qihang Cai; Xuan Wang; Yanbo Yang; Liping Li; Zhenghai Sun; Weiwei Li (Agriculture)
Capsicum frutescens is a valuable economic crop that is widely cultivated for its unique flavor and rich nutritional content. While some studies have shown differences in flavonoid content among different chili species, the mechanism by which changes in flavonoid composition lead to fruit color variations in C. frutescens remains underreported. We performed transcriptomics and widely targeted metabolome sequencing on three different growth stages of the C. frutescens fruit and analyzed the data to better understand the mechanism of color change. Based on previous research on the genes that regulate flavonoid compounds and the MBW complex, we have identified a total of 28 core genes related to flavonoid biosynthesis and 8 genes that may be related to flavonoid synthesis. Through extensive targeted metabolomic analysis, 581 differential metabolites were identified, including 43 flavonoids. Most anthocyanins, flavonols, and flavonoids were found to be more abundant during the immature fruit stage, which we presume is associated with the differential expression of genes involved in flavonoid biosynthesis and regulation. These findings provide a useful reference for understanding flavonoid synthesis and the accumulation of fruits in C. frutescens.